Effect of high hydrogen enrichment on the outer-shear-layer flame of confined lean premixed CH4/H2/air swirl flames. (17th May 2021) - Mao, Runze; Wang, Jinhua; Zhang, Weijie; An, Zhenhua; Lin, Wenjun; Zhang, Meng; Huang, Zuohua
Abstract: In this study, we investigated the H2 -induced transition of confined swirl flames from the "V" to "M" shape. H2 -enriched lean premixed CH4 /H2 /air flames with H2 fractions up to 80% were conducted. The flame structure was obtained with Planar Laser-Induced Fluorescence (PLIF) of the OH radical. Flow fields were measured with Particle Image Velocimetry (PIV). It was observed that the flame tip in the outer shear layer gradually propagated upstream and finally anchored to the injector with the hydrogen fractions increase, yielding the transition from the "V" to "M" flame. We examined the flame structures and the flame flow dynamics during the transition. The shape transition was directly related to the evolution of the corner flame along the outer shear layer. With H2 addition, the outer recirculation zone first appeared downstream where the corner flame started to propagate upstream; then, the recirculation zone expanded upward to form a stable "M" flame gradually. The flow straining was observed to influence the stabilization of the outer shear layer flame significantly. This study can be useful for the understanding of recirculation-stabilized swirling flames with strong confinement. The flame structure and the flow characteristics of flames with a high H2 content are also valuable for model validation. Highlights: Hydrogen-induced transition from "V" to "M" flame is investigated with up to 80% H2 . The formation of "M" flames is strongly related to the OSL flame. The ORZ appears, grows and decreases in size and strength during the transition. The OSL flame can be unstable which influences the ORZ and turbulence therein. The flow straining affects the OSL flame stabilization.